2020
DOI: 10.1093/ijnp/pyaa019
|View full text |Cite
|
Sign up to set email alerts
|

Brain Functional Connectivity Correlates of Response in the 7.5% CO2 Inhalational Model of Generalized Anxiety Disorder: A Pilot Study

Abstract: Background The 7.5% CO2 inhalational model can be used to explore potential treatments for generalized anxiety disorder. However, it is unknown how inter-individual variability in the functional architecture of negative affective valence systems might relate to anxiogenic response in this model. Methods A total of 13 healthy volunteers underwent functional magnetic resonance imaging during a passive emotional face perception … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The current findings suggest this model might through further experiments provide insight into the mechanisms behind anxiety‐balance comorbidity. This is supported by evidence that subjective anxiety during the CO 2 challenge is positively associated with connectivity between the ventromedial prefrontal cortex and the amygdala as well as having negative associations between the midcingulate cortex and the amygdala (Huneke et al, 2020 ). The behavior‐related amygdala activity potentially implicates balance‐related networks such as the parabrachial nucleus network (Stins et al, 2009 ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The current findings suggest this model might through further experiments provide insight into the mechanisms behind anxiety‐balance comorbidity. This is supported by evidence that subjective anxiety during the CO 2 challenge is positively associated with connectivity between the ventromedial prefrontal cortex and the amygdala as well as having negative associations between the midcingulate cortex and the amygdala (Huneke et al, 2020 ). The behavior‐related amygdala activity potentially implicates balance‐related networks such as the parabrachial nucleus network (Stins et al, 2009 ).…”
Section: Discussionmentioning
confidence: 80%
“…The CO 2 challenge model is used to explore treatments for anxiety disorders such as GAD, mimicking the subjective, autonomic, and neuropsychological features (Bailey et al, 2007 ; Garner et al, 2011 ); it is also reactive to pharmacological and psychological treatment (Ainsworth et al, 2015 ; Bailey et al, 2007 ). Importantly, it has been demonstrated that increased functional connectivity between the ventromedial prefrontal cortex and the amygdala can be demonstrated through use of the CO 2 challenge model (Huneke et al, 2020 ). This pathway is important when assessing threat (Mobbs et al, 2007 ), and importantly reduced functional connectivity between the prefrontal cortex and amygdala is observed during threat processing of GAD individuals (Monk et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eligible participants attended an experimental session, comprising 3 segments: baseline pre-conditioning, conditioning and post-conditioning (see Figure 2 ). In the baseline pre-conditioning segment, participants underwent a 7.5% “CO 2 challenge.” Air augmented with 7.5% CO 2 (21% O 2 , balance N 2 ) was administered through an oronasal face mask for 20 minutes, as in previous studies ( Garner et al, 2011 ; Ainsworth et al, 2015 ; Huneke et al, 2020b ).…”
Section: Methodsmentioning
confidence: 99%
“…We use a modi ed version of the generalised anxiety disorder 7-item (GAD-7, (Spitzer et al, 2006)), where each question is represented by a visual analogue scale ranging from "not at all" to "nearly every day". This version of the GAD-7 has been shown to be sensitive to state changes in anxiety with high resolution (Huneke et al, 2020). Further, the GAD-7 questionnaire also captures social anxiety symptoms with good sensitivity (Kroenke et al, 2007).…”
Section: Equipmentmentioning
confidence: 99%